How Perceived Job Insecurity, Voluntary Unemployment and Involuntary Job Loss Shape Couples' Life Satisfaction - Oliver Lipps; Alessandro Di Nallo; Florence Lebert (Journal of Family and Economic Issues, 2025)
To adequately examine the impact of job insecurity and unemployment on life satisfaction in the context of increasing de-standardisation of work arrangements, this study distinguishes nuanced forms of perceived job insecurity and unemployment and integrates them into a single scale for employment instability. These forms comprise (1) no perceived job insecurity, (2) some or (3) severe job insecurity, (4) voluntary unemployment, (5) involuntary unemployment, and (6) other reasons for unemployment. Using dyadic data from the German Socio-Economic Panel (SOEP) for working-age individuals and their partners, both perceived job insecurity and unemployment lead to decreased life satisfaction, with unemployment having a more pronounced impact on life satisfaction. Involuntary reasons for unemployment are more detrimental to life satisfaction than voluntary reasons. Overall, men suffer more from employment instability than women and their employment instability has a stronger impact on their female spouses' life satisfaction than vice versa. The results are interpreted through the lens of `doing gender' and `gender deviation' theory.
Keywords: 300; Germany; Unemployment; Job insecurity; Job loss; Life satisfaction; Employment instability